Digital Literacy in Building a Smart City at Banda Aceh - Muhammad Fazil; Asrul Fahmi; Aflia Riski (International Journal of Engineering, Science and Information Technology, 2022)
The commitment to innovative city-based development must begin with the presence of digital communities that become users and take advantage of all the smarts presented in a smart city. Strengthening digitalization in society by utilizing all the technology offered by the government is interesting to study. Banda Aceh is one of the first cities in Aceh Province to implement the bright city concept successfully; the choice in this study is where the digital literacy strategy in urban communities is the focus. This study aims to describe and analyze digital literacy strategies and their obstacles in building a smart city in Banda Aceh City. This study also uses a descriptive qualitative approach with data collection techniques using observation, interviews, and documentation studies. The data analysis technique used in this study is an interactive model through three main things: data reduction, data presentation, and conclusion. The results of the study found that digital literacy in building a smart city in the Banda Aceh City government by; First, Providing Smart City Technical Guidance, developing intelligent city policies and institutions, conducting readiness analysis and setting targets, introducing smart cities through social media, Cooperating with the community and actively descending to the village, as well as cooperating with other work units, and Infrastructure Development. The obstacles include the government, budget, community, and public organizations. Furthermore, some people are less responsive and use digital literacy for people with disabilities.